Expression of secreted frizzled-related proteins in acute aortic dissection patients and the effects on prognosis - Miao, Huangtai; Li, Xiaoying; Liang, Ying; Tang, Hao; Song, Zihao; Nie, Shaoping (Frontiers in Cardiovascular Medicine, 2023)
Background Secreted frizzled-related proteins (SFRPs) were reported to be involved in cardiovascular diseases. This study aimed to observe plasma SFRP levels in acute aortic dissection (AD) patients and the effects of SFRP expression on AD prognosis. Methods Plasma levels of SFRP1, SFRP2, SFRP3, SFRP4, and SFRP5 were measured in AD patients and non-AD (NAD) patients. The end-point events information of AD patients, including all-cause death and various clinical complications due to aortic dissection, was collected during a 36-month follow-up. Results The SFRP1, SFRP2, SFRP3, and SFRP4 levels were increased in AD patients compared with those in NAD patients, while the SFRP5 concentrations were decreased. No differences in any of the SFRP levels were observed between the type A group and the type B group. The AD patients with end-point events exhibited higher SFRP1, SFRP2, SFRP3, and SFRP4 concentrations but lower SFRP5 levels than the patients without end-point events. In addition, the AD patients were divided into a high group and a low group based on the median SFRP levels, and Kaplan-Meier analysis revealed that the AD patients with high SFRP1, SFRP2, SFRP4, or SFRP5 levels had a better prognosis than those with low levels. However, the AD patients with high SFRP3 levels exhibited the opposite trends. The binary logistic regression analysis found that SFRP1, SFRP2, SFRP4, and SFRP5 were all negatively correlated with the occurrence of end-point events, while SFRP3 was positively correlated with its occurrence. Conclusions SFRP levels are all changed in acute AD, which may affect the prognosis of AD patients. SFRPs may be a target to improve the prognosis of AD.